Mothering, Masking Up, and Sarah Blake’s Clean Air: A Maternal Ecocritical Reading - Toscano, Carolina (Journal of the Motherhood Initiative for Research and Community Involvement, 2023)
During the last two-plus years, COVID-19 has exposed the fissures in the framework of how societies treat mothers. The pandemic has highlighted issues of motherhood that were already present but artfully disguised. This paper aims to analyze those challenges in the context of a newly published cli-fi thriller novel. Clean Air, by Sara Blake, is a matrifocal novel that tells the story of a mother who survives a climate catastrophe, in which the pollen from trees and plants overtakes the earth. The human beings who survive this event cannot go outdoors without special masks, mirroring our experience during the first months of the pandemic. In this project, I explore how critical issues related to mothering are amplified in the contexts of major social upheavals: pandemics, wars, or in the case of this novel, a major climate crisis. The intersection of ecocriticism and maternal theory provides a valuable lens to analyze maternal anxiety, maternal ambivalence, work-life balance, maternal guilt, grieving daughterhood, and imperfect motherhood, which are all present in the descriptions of this alternate reality. All of these motherhood issues are in the undercurrent of the maternal experience portrayed in this novel. However, I argue that the novel goes further than addressing the problems inherent in how we treat mothers under these circumstances. It provides helpful advice on moving forwards, mothering on your own terms, and choosing happiness, suggesting a path towards accepting ourselves as imperfect mothers and imperfect selves.